OPTIMAL CONTROL OF INVENTORIES TEMPE BUSINESS ON PURE BU YANTI IN MANTUP, Banguntapan, Bantul - Ismoyo, Alen; Lastari, SE.,MM, Siwi; Murdo,M.Si, Drs. Yuri (Management, 2010)
In essence it is a creation or production of additional benefits forms, time and place of the factors of production so that more beneficial to the fulfillment of human needs. The production process can be a means, method or technique of production operations by utilizing the factors of production. The average production business has the same goal of trying to increase sales volume for the benefits received increasing. Therefore, every effort should be given that production in the production process deviation occurs sometimes or things that are less suitable for the purpose of production planning. So to overcome this problem it is necessary for inventory control of production processes under control and running smoothly. Inventory control of raw materials intended to reduce or terminate the existence of irregularities in production. In control production costs and product quality, companies should consider the replacement cost of defective products. With the replacement of defective products, the company akanmampu control the use of raw materials in their production processes. The company also must determine the time of booking or purchase back so there is no shortage of raw soybeans in the company. Keywords : inventories